EFEKTIVITAS INOVASI PELAYANAN PUBLIK PADA GERAI PELAYANAN PUBLIK (GP2) DI KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Kamal Badri; Hasim As’ari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Abstract An effort was made to provide effectiveness for public services provided to the public is to make innovations in the field of services that are appropriate to the environmental needs of the community. In this case, the organizer of the Sub-District Government of Rambah Hilir made an innovation policy for public services to overcoming barriers and organizational needs in the public sector number 76 of 2018 concerning public service outlets. Rambah Hilir Subdistrict is the only Subdistrict in Rokan Hulu that is capable of making innovation breakthroughs in the service sector, but the Rambah Hilir Subdistrict government is still not optimal in its implementation so the results to be achieved have not been maximized. The purpose of this study was to determine the effectiveness of public service innovation at the Public Service Outlet (GP2) of Rambah Hilir District, Rokan Hulu Regency. The theoretical concept used is the Theory of Effectiveness according to Duncan, This theory has three indicators to measure Effectiveness: Achieving Objectives; Integration; Adaptation. This research uses qualitative research with a case study approach and with the required data both primary and secondary obtained through interview, observation, and documentation techniques and then analyzed using qualitative analysis techniques. The results of this study indicate that: first, the Implementation of Public Service Innovations in the Public Service Outlet (GP2) in Rambah Hilir District, Rokan Hulu Regency is still not fully effective. Second, the factors that hinder the effectiveness of Public Service Innovation in Public Service Outlets (GP2) in Rambah Hilir District, Rokan Hulu Regency, namely: human resources, facilities and infrastructure, and district level government support. Keywords: Effectiveness, Service Innovation, Public Services